Species Diversity and Community Structure of Macrobenthos in the Cosmonaut Sea, East Antarctica - Jianfeng Mou; Kun Liu; Yaqin Huang; Junhui Lin; Xuebao He; Shuyi Zhang; Dong Li; Yongcan Zu; Zhihua Chen; Sujing Fu; Heshan Lin; Wenhua Liu (Diversity, 2023)
The Cosmonaut Sea is an under-studied area and a “white spot” for macrobenthos research. Here, we report on the species diversity and community structure of macrobenthos collected using tringle trawls on the 38th Chinese National Antarctic Research Expedition (CHINARE) in the Cosmonaut Sea, East Antarctica. A total of 11 tringle trawls were deployed at different depths across the shelf, slope and seamount of the Cosmonaut Sea. A total of 275 macrobenthic species were found from 207 to 1994 m. The species richness per station varied from 23 to 89. Echinoderms (100 species), arthropods (48 species) and mollusks (36 species) were the most dominant groups. Echinoderms and arthropods dominated in abundance at seamount stations, and echinoderms, arthropods and polychaetes dominated in abundance at slope stations, while bryozoans, corals, ascidians and sponges were abundant on the Cosmonaut Sea shelf. Depth was the major driving force influencing the distribution of macrobenthos. The main components were two core communities. One was dominated by sessile suspension feeders and associated fauna. Variants of this community include sponges and bryozoans. The other core community was dominated by mobile deposit feeders, infauna and grazers–epifauna, which included arthropods and echinoderms. The results showed that the slope (40–50° E, 65–67° S) of the Cosmonaut Sea may be an important area with complex ecological processes. The results of this study contribute to the knowledge of species diversity and communities of macrobenthos in the Cosmonaut Sea and provide monitoring data for future ecosystem health assessments and better protection.